Alinta Krauth, An E-poet: Where Nature and Humans come Together - Yolanda de Gregorio Robledo (Hyperrhiz)
An interview with Dr Alinta Krauth, an Australian artist who merges environmental and animal research with art, using technology to create aesthetic, multispecies interactive experiences.